Quality Control of TH Lever Assy Products Using the Six Sigma Method at PT. IMC Tekno Indonesia - Adi Kusmario (BRIDGE : The Multidisciplinary Research Portal, 2024)
This study discuss about product defects in the TH Lever Assy manufacturing process. Objective from study This is For identify cause and reduce disabled products in the TH Lever Assy production process. Object study This is companies operating in the field producer component plastic resulting precision​ from Injection molding , meanwhile focus research on the TH Lever Assy production process. Study This analyzed use six sigma method with stages Define, Measure, Analyze, Improve, Control (DMAIC), the six sigma method is stages enhancement quality For reach the expected sigma level company . Research result This namely 6 causes happen disabled product that is short mold , burry / flashes , scratch , child part No installed , frash , metal material in plastic . Before sigma level improvement reached 4.32 with DPMO value of 2,445 and after repair reaching the sigma level of 4.31 with DPMO value is 2,428.